Internal Resources that Encourage Students to Engage in Value Co-Creation Activities - Efendi, Ahmad; Awaluddin, Awaluddin; Rahman, M. Akil; Nofri, Okta; Sumarsih, Sumarsih (Jurnal Minds: Manajemen Ide dan Inspirasi, 2024)
There is still debate among academics about the activities and operations of universities and whether they can be equated with business entities. This study analyzes the relationship between student resource factors and university value co-creation activities. Several variables in this research have never been studied in the context of higher education services. This research employs a quantitative approach and involves the participation of 398 students from various universities in Makassar, Indonesia. Data is processed and analyzed using Smart-PLS software. The results showed that student resources, such as student self-efficacy, student education, and student expertise, positively and significantly influenced value co-creation activities in the university environment. The creation of university values must create a positive environment to attract future pupils.